Plasminogen Activator Inhibitor Type-1 Determines Plasmin Formation in Patients with Ischaemic Heart Disease - Pedersen, Ole Dyg; Gram, Jørgen; Jespersen, Jørgen (Thrombosis and Haemostasis, 1995)
The aim of the present study was to find out whether plasminogen activator inhibitor type-1 (PAI-1) controls the formation of plasmin in patients with ischaemic heart disease.We examined PAI activity, PAI-1 antigen, tissue type plasminogen activator (t-PA) activity, t-PA antigen, plasmin-α2-antiplasmin complex (PAP-complex) and fibrin degradation products D-dimer in 62 patients before (unstimulated) and after infusion of l-desamino-8- D-arginine vasopressin (DDAVP; stimulated). DDAVP was used in a standardized dose to trigger the release of t-PA from the vascular endothelium.We observed that under basal conditions (unstimulated) median plasma t-PA activity for the whole group of patients was 86.5 mlU/ml (0-900), and after stimulation 2550 mlU/ml (0-6800), P <0.0001; median plasma concentration of t-PA antigen was 14.7 ng/ml (7.0-115.5) under basal conditions, and after stimulation 34.1 ng/ml (15.8-58.6), P <0.0001; median plasma PAI activity was 16.9 IU/ml (1.5-144.8) under basal conditions, and after stimulation 3.1 IU/ml (0-118.5), P <0.0001; median plasma concentration of PAI-1 antigen was 21.5 ng/ml (8.1-132.2) under basal conditions, and after stimulation 14.9 ng/ml (4.8-149.0), P <0.0001; the median plasma concentration of PAP-complex was 469.5 ng/ml (185.0-1802.0) under basal conditions, and after stimulation 695.5 (243.0-2292.0), P <0.0001; median plasma concentration of D-dimer was 298.0 ng/ml (103.0-948.0) under basal conditions, and after stimulation 296.5 ng/ml (97.0-917.0), P <0.0008.Under basal conditions plasma PAI activities and plasma concentrations of PAI-1 antigen were both significantly negatively correlated with plasma concentrations of PAP-complex (rs = -0.32; P <0.02 and rs = -0.42; P <0.002, respectively). After stimulation of the fibrinolytic system by infusion of DDAVP, plasma PAI activities and plasma concentrations of PAI-1 antigen were also significantly negatively correlated with plasma concentrations of PAP-complex (rs = -0.41; P <0.002 and rs = - 0.33; P <0.009, respectively).Our results indicate that PAI-1 regulates formation of plasmin in patients with ischaemic heart disease. These observations support that PAI-1 may play a critical role in the evolution of thrombosis.